If it's not what You are looking for type in the equation solver your own equation and let us solve it.
20=11+3q
We move all terms to the left:
20-(11+3q)=0
We add all the numbers together, and all the variables
-(3q+11)+20=0
We get rid of parentheses
-3q-11+20=0
We add all the numbers together, and all the variables
-3q+9=0
We move all terms containing q to the left, all other terms to the right
-3q=-9
q=-9/-3
q=+3
| 9x-5(3x+12=-24 | | 15r−6r−3=−2r | | 2x-5=7x+7-6x | | 6x-(x-2)=x-2 | | 4/19=8/a | | 6(p+8)+8(-4-p)=22 | | 18+5x=73 | | 7-5v=23 | | 157+-11x=64 | | 25=-5(3x-4) | | 6x+5x=-3 | | 11^b-3=5b | | .25x+3=0-7 | | 3(4x-7)=7 | | 11b-3=5b | | N+n*n=1 | | 12-4+3x=11 | | 4(-7+6k)+7k=3 | | 3x+17-1/2x-5=180 | | .25x+3=-7 | | 5x-2+35=4 | | 3g-47=-7 | | 3,616=32(p+35) | | 3x+5-7x=19+2 | | 5×(h×9)=(5×h)×9 | | -9=8-y | | p-7.53=32.47 | | 14-8x=2+8x | | 3y-2.6=0.8 | | x-1=x+2=2x-3 | | 20+y=17 | | x(x-1)-5(x+2)=2 |